Quasi-two-dimensional convective lines with leading precipitation: dynamics inferred from idealized numerical simulations - Parker, Matthew D., author (Colorado State University. Libraries, 2002)
Recent work has identified three types of linear mesoscale convective systems (MCSs): those with convective lines and either trailing (TS), leading (LS), or parallel (PS) stratiform precipitation, the latter two of which have received comparatively little study. This publication describes a study in which the author used idealized numerical simulations to investigate the basic structures of convective lines with leading precipitation, and addresses the dynamics governing individual air parcels' accelerations within them. It appears that, although unconventional, systems with inflow passing through their line-leading precipitation can be stable and long-lived. Lower tropospheric inflowing air in the simulations is destabilized by lifting and by the vertical profile of evaporation and melting within the pre-line precipitation. This air then ascends, overturns in deep updrafts, and subsequently carries its water content forward from the convective line, where it gives rise to the leading precipitation region. Although relatively strong wind shear in the middle and upper troposphere accounts for a component of the downshear acceleration, and hence overturning, of air parcels in the simulated updrafts, a mature system with leading precipitation also renders both persistent and periodic pressure anomalies that contribute just as much. Many of these accelerations, which govern the overall system structure, are largely transient and are lost when averaged over multiple convective cycles. This publication explains the dynamics that govern the transient updrafts and downdrafts within the systems, including a precipitation cut-off mechanism that governs their multicellular periods. The text also addresses the applicability of several theoretical squall line models to convective lines with leading precipitation, and briefly documents the simulations' sensitivities and the basic evolutions between convective modes produced in the model.
Summer 2002.
Also issued as author's dissertation (Ph.D.) -- Colorado State University, 2002.
Keywords: Convection (Meteorology); Numerical weather forecasting.